Bacteriological quality of bottled natural mineral waters commercialized in Hungary - Varga László (FOOD CONTROL, 2011)
The purpose of the present study was to examine the bacteriological quality of bottled natural mineral waters sold in Hungary because, in recent years, there has been a tremendous increase in consumer demand for these products in the country. In total, 492 samples of domestic and imported brands of carbonated and non-carbonated mineral waters (246 samples each) were purchased from retail outlets, and were then screened for the presence of the following indicator and potentially pathogenic bacteria: spore-forming sulfite-reducing anaerobes (clostridia), total coliforms. Escherichia coli, Enterococcus spp., and Pseudomonas aeruginosa. Heterotrophic plate counts (HPC) were also determined by incubation at 37 degrees C for 24 h and at 22 degrees C for 72 h. The data generated were compared to the reference criteria set by Directive 2009/54/EC of the European Parliament and the Council of the European Union on the exploitation and marketing of natural mineral waters. The results showed that 5.3% and 10.2% of the carbonated and non-carbonated mineral water samples tested, respectively, were positive for at least one of the specific indicator or potentially pathogenic bacteria. Overall, a total of 38 sample units (7.7%) failed to comply with the standards set by Directive 2009/54/EC. None of the samples were judged noncompliant with current regulations on the basis of the presence of HPC bacteria at levels reaching or exceeding the acceptability limit (i.e., 100 CFU/ml at 22 degrees C or 20 CFU/ml at 37 degrees C) because the analyses were not carried out within 12 h after bottling, as required by Directive 2009/54/EC. The findings of this study highlight the need for a more stringent self-control by some producers of mineral water. In addition, a more systematic surveillance by the official authorities of food control is also necessary. (C) 2010 Elsevier Ltd. All rights reserved.